The Influence of an Ecopedagogical Approach in Social Studies Learning on Students' Ecological Intelligence - Dwi Bahtiar El Rizaq, Agung; Sujatno; Sea Thearith; Sorn Sovanreach (International Journal of Geography, Social, and Multicultural Education, 2024)
Environmental issues are the center attention to ensure the continuation of sustainable development. Ecological intelligence is one of the important abilities that students have. One way to intervene in students' ecological intelligence can be done through learning with an ecopedagogical approach. This research aims to determine the effect of the ecopedagogical approach in social studies learning on students' ecological intelligence. This research uses a quantitative type using a quasi-experimental method. Sampling in this study used a purposive sampling technique, with a total sample of 60 students at MTs Negeri 1 Pamekasan who were divided into 2 (two) classes, namely class VII A as the control class, and class VII C as the experimental class. Based on the results of the research that has been carried out, the following conclusions can be drawn; In the experimental class the average N-Gain was 71.26. Meanwhile, the control class had an average N-Gain of 48.11. Then the t-test shows that the sig value. (2-tailed) of 0.000<0.05 which can be concluded that there is a significant (real) difference in effectiveness between the effect of using an ecological approach in social studies learning on students' ecological intelligence compared to conventional learning. Finally, an ecopedagogical approach in social studies learning needs to be developed to foster sensitivity regarding the complexity of environmental problems in order to contribute to environmental issues.